Penerapan Sistem Informasi Bisnis dalam Proses Pengelolaan Arsip Secara Digital di PT Pelindo Terminal Petikemas - Alsya Puteri Pradanti; Rusdi Hidayat Nugroho (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The development of technology and information in the business world has experienced rapid progress due to globalization. Technological developments are utilized in various sectors of life, one of which is the implementation of a business archive system. PT Pelindo Terminal Petikemas uses digital archive management in document/archive management to improve the quality of company administration. As an intern, the writer has an obligation to help with document management, inventory operations and reporting as well as the implementation of information technology. Apart from that, the MyInvent application is also used in the company's daily operations. The methods used in this research are direct observation, interviews, direct and active involvement and literature review. The results that the author got regarding the obstacles that occurred at PT Pelindo Terminal Petikemas were the lack of employee understanding of the new system which caused employees to have to adapt to the system and increase their skills